The angioarchitecture of brain arteriovenous malformations and its' associa tion with intracranial haemorrhage: An analysis - Shibani A., Kandhai (Universiti Sains Malaysia, 2007)
Title: The angioarchitecture of brain arteriovenous malfonnations and its' association with intracranial haemorrhage: an analysis Introduction and objectives: Central nervous system arteriovenous malfonnation (AVM) is a vascular malfonnation of the brain and consists of a tangle of veins and arteries without an intervening capillary bed. It predominantly affects young male patients and presents with different clinical manifestations namely headache, seizures, neurological deficit and intracranial haemorrhage. The patients who present acutely with intracranial bleed have a significant morbidity and mortality. Thus, the aim is to study the angioarchitecture ofBA VM and determine intracranial bleed. This study also enabled us to look for the association between the volume of haematoma and the architecture of the brain arteriovenous malfonnation. The correlation between the features and risk of intracranial bleed is invaluable in predicting the behaviour of BA VM. Methodology: This was a cross sectional study where patients who attended the Department of Radiology were retrospectively collected from the'-year 2000. A total of 58 patients were included after excluding dural arteriovenous fistula and brain haemangiomas. The nidal size of the lesion and its maximum diameter were measured on cerebral angiogram. Venous drainage, feeding arteries aneurysms and location were further evaluated on cerebral angiogram and CT scan/MRI. The association between the angioarchitecture of BA VM and intracranial haemorrhage were analysed using multivariate analysis. The other objective to evaluate the association between angioarchitecture and volume of haematoma was detennined using univariate model. Results: In HUSM, BAVM was seen predominantly in a young male patient with a mean age of 26.67 (SD ±12.96). Small nidal size (p-value = 0.000), deep location (pvalue = 0.000) was found to be predictors of intracranial bleed. And deep venous drainage was significant at a univariate level only due to a small sample size. All patients with brain arteriovenous malfonnation and coexisting intracranial aneurysms presented with intracranial bleed. The angioarchitecture of BA VM detennining the volume of haematoma was not found to be significant statistically, but on clinical interpretation diffuse bleed was seen in 69 % deeply located, 63 % small sized and 66.7 % deep draining vein, 70 % deep arterial feeders and presence of coexisting aneurysms.